1986
DOI: 10.1007/bf03179368
|View full text |Cite
|
Sign up to set email alerts
|

Biological activity of earthworm casts: An assessment of plant growth promotor levels in the casts

Abstract: Biochemical analyses and auxin and cytokinin bioassays were performed to test the biological activity of wormcasts. Both cellulose paper pulp and soil casts of Lampito mauritii were rich in ammonia, urea, organic carbon content, organic matter, soluble phosphorus and ionic potassium levels. The total nitrogen content of the soil remained unaffected by worm activations. The casts of Lampito mauritii, Pheretima elonl/ata, Pontoscolex corethrurus and Ocnerodrilus occidentalis had greater urea levels relative to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(58 citation statements)
references
References 12 publications
1
56
0
Order By: Relevance
“…Vermicompost contains plant-growth-regulating materials, such as humic acids (Senesi et al 1992;Masciandaro et al 1997;Atiyeh et al 2002), auxins, gibberellins, and cytokinins (Krishnamoorthy and Vajrabhiah 1986;Tomati et al 1988Tomati et al , 1990Singh et al 2008). These regulators are produced through the action of earthworms and microbes such as fungi and actinomycetous bacteria, which increase the plant growth and yield of many crops (Tomati et al 1988;Atiyeh et al 2002).…”
Section: Dry Weight Of Total Aboveground Biomassmentioning
confidence: 99%
“…Vermicompost contains plant-growth-regulating materials, such as humic acids (Senesi et al 1992;Masciandaro et al 1997;Atiyeh et al 2002), auxins, gibberellins, and cytokinins (Krishnamoorthy and Vajrabhiah 1986;Tomati et al 1988Tomati et al , 1990Singh et al 2008). These regulators are produced through the action of earthworms and microbes such as fungi and actinomycetous bacteria, which increase the plant growth and yield of many crops (Tomati et al 1988;Atiyeh et al 2002).…”
Section: Dry Weight Of Total Aboveground Biomassmentioning
confidence: 99%
“…This meant that other mechanisms than mineralization were involved. The stimulation by earthworms of bacteria producing phytohormone-like compounds (Krishnamoorthy and Vajranabhaiah, 1986) has been suggested. Auxin-like compounds have indeed been identified in earthworm casts (Muscolo et al, 1998(Muscolo et al, , 1999.…”
Section: Introductionmentioning
confidence: 99%
“…dehydrogenase activity) (Arancon et al, 2006), the inhibition or reduction of plant diseases (Szczech, 1999;Szcech and Smolinska, 2001) and the production of plant-growth regulating substances. In this sense several studies have reported some kind of hormonelike activity of vermicompost (Krishnamoorthy and Vajranabhiah, 1986;Tomati et al, 1988;El Harti et al, 2001;Atiyeh et al, 2002). Canellas et al (2002) and Quaggiotti et al (2004) reported the presence of certain plant hormones such as indoleacetic acid adsorbed into the low-weight humic substances extracted from earthworm faeces.…”
Section: Introductionmentioning
confidence: 99%